Escritório de projetos da diretoria de coordenação da Usina de Itaipu Binacional: proposta de modelo de seleção e priorização de projetos - Correia, Rafael Antonio dos Santos (2018)
This paper´s purpose means to show a proposal of a project portfolio priorization method for the Coordenation Department of Itaipu Dam, with the goal to be an objective and strategical tool. The process, composed by five steps, uses successful project attributes and project selection criteria, evaluated together using the Analytical Hierarchy Process Method, by using data obtained on a online survey focused on project management professionals and the companies project management office staff. Besides, offers ways to the high management to strategically situate the portfolio, by evaluating the projects using the strategical pillars of the Department. Finally, demonstrate the surveys results and the developing of the process steps through the obtained data.